Building Competitiveness Through Visual Identity as MSMEs Empowerment in the Permata Sawon Indah Center, Buduran Village: Membangun Daya Saing Melalui Identitas Visual Sebagai Pemberdayaan UMKM di Sentra Permata Sawon Indah Desa Buduran - Rangga Aji Nugroho; Daisy Marthina Rosyanti (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) requires a strategic approach to remain competitive in a dynamic market. One relevant strategy is the strengthening of visual identity as a representation of business values and characteristics. This community service activity was conducted at the MSME center PERMATA SAWON INDAH in Buduran Village, aiming to enhance competitiveness through training and practical workshops on banner creation as a visual identity medium. The method employed was participatory-educational, involving assessment, material delivery, and hands-on design practice. The results indicate an increased understanding among MSME actors regarding the importance of visual identity and basic technical skills in designing representative business banners. This activity is expected to serve as a model for visual branding empowerment that can be replicated in other MSME communities.